PELATIHAN DAN PEMANFAATAN INTERNET BRANDING SEBAGAI MEDIA PROMOSI DAN CROWD FUNDING UNTUK KOMUNITAS PENDIDIKAN "RUMAH BELAJAR" DI KABUPATEN MOJOKERTO - Suryawinata, Mohammad (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2017)
Rumah Belajar is one of the society movement that engaged in education which located in Gedeg District, Mojokerto. The activity at Rumah Belajar is designed for free of charge. Rumah Belajar was established to shield teenager from the rising of negative influences. In today’s digital era, many problems appear, at the same time new opportunities arise. One of them is the teenagers tendency to use gadgets such as laptops or smartphones in a high intensity. Some promotional techniques have been done, but until now Rumah Belajar is not widely known by the public. The problems of the partner in this program which is Rumah Belajar is not yet known widely by society. Rumah belajar is a new innovation in non formal education. The students in Rumah Belajar for now is below 20. Actually, Rumah Belajar’s capacity can be used for 40 students or so. The Other problems which is related to the unpopularness of Rumah Belajar is the lack of donation from the donors. This causing the deficit of Rumah Belajar’s operational cost. So some of the teachers do not get any salary. In connection with the major problems that have been mentioned, this program will offer a solution that is expected to solve the problems of partners. The main method used is to use the Internet Branding to create and improve the reputation of Rumah Belajar in the digital age. Internet branding are offered to create a system that consists of a website that will be linked with social media to get some crowdfunding. The results of the community service program are able to build brand partners digitally and publicize Rumah Belajar’s movement to the wider community. In addition, the results of this program will be made as teaching materials on Web-Based Application Development course at the University of Muhammadiyah Sidoarjo and will be disseminated through electronic media so it can be accessed by every people.